WHEN GOODWILL IS NOT ALWAYS GOOD: AN ANALYSIS OF THE IMPACT OF INTANGIBLE ASSETS ON THE VALUE OF INDONESIAN MEDIA COMPANIES - Muhammad Farid Alrasyid; Inung Wijayanti; Huda Trihatmoko; Laras Rayi Saraswati (Journal of Social and Economics Research, 2025)
This study aims to analyze the effect of goodwill and financial performance on the firm value of media companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The results of the study show that negative goodwill has a significant impact on company value with a significance value of 0.002, indicating the need for proper financial reporting management to reduce investor distrust. Meanwhile, profitability, measured by Return on Assets (ROA) and Return on Equity (ROE), does not have a significant effect, with significance values of 0.403 and 0.970, respectively. This suggests that asset management efficiency and the ability to generate profits still need improvement. Leverage, measured by the Debt to Asset Ratio (DAR), has a significant positive effect on firm value with a significance value of 0.044, indicating that appropriate debt utilization can enhance firm value. In addition, the activity ratio, measured by Total Asset Turnover (TATO), also has a significant positive effect with a significance value of 0.028, reflecting the company's efficiency in utilizing assets. These findings emphasize that companies should prioritize managing goodwill, leverage, and asset efficiency to improve firm value in the eyes of investors.